Impact of oenological processing aids and additives on the genetic traceability of 'Nebbiolo' wine produced with withered grapes. (January 2022) - Gambino, Giorgio; Ferrero, Lorenzo; Scalzini, Giulia; De Paolis, Camilla; Paissoni, Maria Alessandra; Río Segade, Susana; Giacosa, Simone; Boccacci, Paolo; Rolle, Luca
Graphical abstract: Highlights: Oenological processing aids and additives played a role in removing DNA from wine. Treatments with the highest oenological impact caused the highest loss of DNA. Loss of DNA caused by aging is lower compared to the loss linked to fining agents. SNP-based assay failed in 'Nebbiolo' wines treated with bentonite and gelatine. Abstract: 'Nebbiolo' is a well-known grapevine variety used to produce prestigious monovarietal Italian red wines. Genetic traceability is an important tool used to protect the authenticity of high-quality wines. SNP-based assays are an effective method to reach this aim in wines, but several issues have been reported for the authentication of commercial wines. In this study, the impact of the most common commercial additives and processing aids used in winemaking was analysed in 'Nebbiolo' wine using SNP-based traceability. Gelatine and bentonite had the strongest impact on the turbidity, colour and phenolic composition of wines and on residual grapevine DNA. The DNA reduction associated with the use of bentonite and gelatine (>99% compared to the untreated control) caused issues in the SNP-based assay, especially when the DNA concentration was below 0.5 pg/mL of wine. This study contributed to explaining the causes of the reduced varietal identification efficiency in commercial wines.